Existential Experimentation: An Exploration Of Two Clients Relating To The Theme Of 'Naked and Dangerous' (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
This paper explains the principles underpinning the framework of an existential-phenomenologically informed intervention, with focus on two case studies to demonstrate this model, both with reference to the theme naked and dangerous.
Keywords: Existential phenomenological intervention; existential experimentation; principles; naked; dangerous; goals